The John Hopkins atlas of surgical pathology - Epstein, Jonathan I.; Churchill Livingstone (Publisher) ([S.I.] : Churchill Livingstone, 1999)
(Producer) Provides approximately 4000 images with nearly 1500 different lesions. Divided into two sections. The pattern recognition section is organized by organ and lesion group, and presents full-color images and text descriptions of lesions. The self assessment section is designed to test recognition skills
Title from disc label
System requirements: IBM compatible, 486/66 MHz processor; 12 MB of RAM, 8 MB of free hard disk space; Microsoft Windows 3.x, Windows 95, or Windows NT; 15 in. 16-bit SVG color monitor (16-bit required); 2X CD-ROM drive; sd. card (only recommended for the tutorial)
System requirements: Macintosh, 68040 processor; 12 MB of RAM, 8 MB of free hard disk space; System 7.x; 14 in. SVGA color monitor (thousands of colors required); 2X CD-ROM drive
Keywords: Pathology, Surgical -- atlases